THE ROLE OF SODIUM ION IN PHOSPHORUS REMOVAL WHEN ALUM IS USED AS A COAGULANT - A. Hasan, Ali (Journal of Engineering and Sustainable Development, 2022)
Jar examination was applied to treat dairy water by using alum as a coagulant. Synthetic samples similar to actual wastewater were prepared from real dairy products to achieve the work. All tests of characteristics have been performed according to American Public Health Association (APHA), American Water Works Association (AWWA), and Water Environment Federation (WEF). The apparatus used in this study is the Jar test model JLT 6 Leaching test VELP Scientifica, with all kits and tools that could complete the work. The results showed the ability of aluminum sulfate to remove phosphorous from dairy wastewater by up to 95%. This resulted in an optimum aluminum dose equal to 0.5 mg / l at 20°C, and a gradient speed of 1076.915 seconds. -1. These results correspond to the role of the sodium ion in removing contaminants as a catalyst; the sodium ion concentration that contributed to this activity was 60 mg per liter, representing 23.07% of the initial concentration. The main goal of this article, it’s how can exploit the factors and circumstances adjacent to reducing pollutants without increasing aluminum dosages.